Adequacy of Public Information for Meaningful E-Participation in Policy-Making - Inna Junaenah; Abd Shukor Mohd Yunus; Normawati Hashim (University of Jember, 2022)
Within the first two years of COVID-19’s exposure, countries around the world mitigated, among other things, social mobility control, resulting in other limitations on fundamental rights, such as freedom of movement and peaceful assembly. Within the rights restrictions, the desire of citizens to satisfy their desire for information and exercise their right to free expression was insatiable. The authors argue that citizens deserve access to sufficient information in order for them to have a meaningful right to participate. At the same time, electronic means can be an additional feature to channel public participation in policy-making. Regrettably, the primary platform adopted in Human Rights laws in operationalizing the right to participate in public affairs remains minimal to coexist meaningful e-participation embarked on the adequacy of the right to information based on Human Rights (HR) standards. This study aims to answer how a justification for meaningful e-participation in law-making can be defined. It also queries which framework can provide sufficient public information based on a rights-based approach. The study leverages the convention of civil and political rights (ICCPR) as the primary legal instrument for a qualitative doctrinal approach. The study suggests that adequate information should be in one package with e-participation to optimize the enjoyment of the right to participate in policy-making. Keywords: Law-Making, meaningful e-Participation, Right-Based, Right to Information